2012
DOI: 10.1186/1477-3155-10-26
|View full text |Cite
|
Sign up to set email alerts
|

Immunoliposome-PCR: a generic ultrasensitive quantitative antigen detection system

Abstract: BackgroundThe accurate quantification of antigens at low concentrations over a wide dynamic range is needed for identifying biomarkers associated with disease and detecting protein interactions in high-throughput microarrays used in proteomics. Here we report the development of an ultrasensitive quantitative assay format called immunoliposome polymerase chain reaction (ILPCR) that fulfills these requirements. This method uses a liposome, with reporter DNA encapsulated inside and biotin-labeled polyethylene gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Upon binding to the target antigen, the liposome bursts to release the reporter DNA, which permits the target protein to be quantified using real-time PCR. [129]…”
Section: Applications Of Nanoscale Avidin Systems In Diagnosis Andmentioning
confidence: 99%
“…Upon binding to the target antigen, the liposome bursts to release the reporter DNA, which permits the target protein to be quantified using real-time PCR. [129]…”
Section: Applications Of Nanoscale Avidin Systems In Diagnosis Andmentioning
confidence: 99%
“…HIV-1 DNA ILPCR 0.013 pg/ml 2012 [83] HIV-1 gp41 Biomimetic sensor (epitope imprinted hydrophilic polymer-coated quartz crystal microbalance) 2 Â 10 3 pg/ml 2012 [84] HIV-1 p24 BCA-MMP 0.1 pg/ml 2012 [85] HIV-1 p24 ELISA 1 Â 10 3 pg/ml 2012 [85] HIV-1 p24 BCA-based microplate method assays 1 pg/ml 2012 [85] HIV-1 p24 Amperometric immunosensor (using GNP, MWCNTs and an AEP) 6.4 pg/ml 2011…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…The application of DNA-encapsulated liposome has been reported in a study, where a modified version of iPCR, called as immunoliposome-PCR, has been utilized to measure the concentration of carcinoembryonic antigen (CEA) in human serum. This study showed that this novel method is 1,500 times more sensitive than common methods of CEA detection [ 56 ]. Similarly, immunoliposome-LAMP method can be designed to considerably enhance the detection limit of iLAMP.…”
Section: The Hypothesis and Its Evaluationmentioning
confidence: 99%